The environmental pollution caused by cemeteries and cremations: a review (2022)
In recent years the funeral industry has drawn attention from the scientific community concerning the potential pollution of the environment and the urban environment. In this review, the pollution caused by the cemeteries and crematoria around the world was addressed. The traditional burial leads to the production of ions, in the form of organic and heavy metals, bacteria, fungi, and viruses, that spread along with the soil and underwater. The crematoria produce small particles, trace gases (SOx, NOx, CO), and toxic organic volatiles. The effluent generated by both methods can lead to several environmental problems and further threaten human health. The current solution for the cemeteries in the development of a system in which effluent generated by the traditional burials are collected and treated before realizing in the environment. In addition to that, the green burial should be an alternative, since the corpse does not go through the embalming process, thus eliminating the presence of any undesired chemicals, that are further leached onto the environment. The crematoria should be employed as it is, however, the gas treatment station should be employed, to ensure the minimization of the impact on the environment. Last, future researches regarding the treatment of the cemeteries leached still need to be explored as well as the optimization and further development of the crematoria gas treatment process.